Private and Public Pensions Schemes: A Case of Vertical Segmentation - Carlo Mazzaferro (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1993)
This work develops an overlapping generations model in order to analyze a transition to a partial privatization of the social security system. We find that such a reform induces a vertical segmentation in the market of pension schemes. Moreover the redistributive aim of the government is limited by the possibility to switch from the private to the public pension scheme.
Keywords: 330